From principle to practice: community consultation regarding access to Indigenous language material in archival records at the State Library of New South Wales. Issue 3 (1st September 2016) - Nicholls, Sophie; Booker, Lauren; Thorpe, Kirsten; Jackson, Melissa; Girault, Clement; Briggs, Ronald; Jones, Caroline
Abstract: In the context of Indigenous languages, archival science in Australia continues to move from a theoretical framework of considering record subjects as third parties to a 'participants model'. In a participants model framework record subjects are considered co-creators and custodians of the intellectual property of the record. However, the shift from theory to practice is still an under-described challenge currently facing archival professionals. This article reports on an experience of applying guidelines developed by First Languages Australia (FLA) and National and State Libraries of Australasia (NSLA) aimed at enhancing the rights of Indigenous Australians over records that contain Indigenous language material. A team of researchers from the State Library of New South Wales (SLNSW) Indigenous Services branch and Western Sydney University engaged with four Indigenous language groups to evaluate records containing Indigenous language material held at the SLNSW. On viewing the archival records of Indigenous language material members of community groups expressed a diversity of opinions and suggestions. This feedback was grouped by the authors into the following themes: painful remembrance of the provenance of the archival record, evaluations of the value of the documents, custodianship and use of the language material, and access to the SLNSW records. The authors found that participants in the study substantially shaped the process of implementing the protocols.